(untitled) (International journal of medical sciences, 2026)
This article analyzes the clinical characteristics, diagnostic principles, and modern treatment approaches for open wounds of the maxillofacial region. The etiology of injuries, the degree of tissue damage, and the risk of infection are shown to be the main factors in selecting appropriate treatment tactics. Timely and anatomically accurate primary surgical management plays a decisive role in preventing complications. Comprehensive treatment includes antibacterial therapy, local antiseptics, reconstructive surgery, and rehabilitation measures. The use of physiotherapy and functional exercises contributes to faster recovery of mastication and speech functions. The results demonstrate that a staged comprehensive approach reduces the frequency of infectious complications and improves functional and aesthetic outcomes. Early diagnosis and high-quality primary surgical treatment also significantly improve the patient’s quality of life and social adaptation.